Health, illness, and medicine : ethnographic readings - Mishra, Arima (New Delhi : Orient Blackswan, 2010)
Contributed articles; with reference to India.
Includes bibliographical references and index.
Keywords: Social medicine -- India; Medical anthropology -- India